Comparative Assessment of Bone Mineral Density and Body Composition Via DEXA in Individuals with and without Osteoporosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Osteoporosis is a systemic skeletal disease characterized by low bone mineral density (BMD) and structural deterioration of bone tissue, leading to increased fracture risk. Dual-Energy X-ray Absorptiometry (DEXA) remains the gold standard for diagnosing osteoporosis and assessing body composition. This study aims to compare BMD and body composition parameters between individuals with and without osteoporosis. A total of 372 subjects aged 50 years and above underwent DEXA scanning. Results indicate significantly lower BMD values in osteoporotic individuals compared to controls. Differences in body composition, including fat and lean mass distribution, were also observed. These findings highlight the importance of integrated assessment of BMD and body composition for early diagnosis and management of osteoporosis.